Improving the meat quality of Blesbok (Damaliscus Dorcas Phillipsi) and Springbok (Antidorcas Marsupialis) through enhancement with inorganic salts - Du Buisson, Petro-Mare (Stellenbosch : University of Stellenbosch, 2006)
Thesis (Msc (Animal Sciences))--University of Stellenbosch, 2006.